2012
DOI: 10.1016/j.bbadis.2012.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of nine novel naturally occurring human melanocortin-3 receptor mutations

Abstract: The melanocortin-3 receptor (MC3R) is a member of family A rhodopsin-like G protein-coupled receptor. Mouse genetic studies suggested that MC3R and the related MC4R are non-redundant regulators of energy homeostasis. Lack of Mc3r leads to higher feed efficiency and fat mass. However, until now only a few MC3R mutations have been identified in humans and the role of MC3R in the pathogenesis of obesity was unclear. In the present study, we performed detailed functional studies on nine naturally occurring MC3R mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…Further studies on the interactions between these mutants and molecular chaperones might help to understand the forward trafficking mechanism of MC4R. In the related MC3R, we showed that mutations at T280, corresponding to M241A K242A G243A A244G A244G I245A T246A L247A T248A I249A L250A L250A I251A G252A V253A F254A V255A V256A C257A W258A A259G A259G P260A F261A F262A L263A H264A L265A I266A I266A F267A F267A Y268A I269A I269A S270A 100 T246 in the MC4R, decreased cell surface expression (Yang & Tao 2012).…”
Section: Discussionmentioning
confidence: 90%
“…Further studies on the interactions between these mutants and molecular chaperones might help to understand the forward trafficking mechanism of MC4R. In the related MC3R, we showed that mutations at T280, corresponding to M241A K242A G243A A244G A244G I245A T246A L247A T248A I249A L250A L250A I251A G252A V253A F254A V255A V256A C257A W258A A259G A259G P260A F261A F262A L263A H264A L265A I266A I266A F267A F267A Y268A I269A I269A S270A 100 T246 in the MC4R, decreased cell surface expression (Yang & Tao 2012).…”
Section: Discussionmentioning
confidence: 90%
“…After blocking with PBS-IH containing 5% BSA for 1h, the cells were then incubated with the primary antibody anti-HA.11 (Covance, Princeton, NJ, USA), which was diluted 1:100 in PBS-IH containing 5% BSA, for another 1 h. The cells were washed once with 0.5% BSA in PBS-IH and then incubated with the secondary antibody Alexa Fluor 488-labeled goat anti-mouse IgG (Invitrogen) for 1 h. The cell surface expression of WT and mutant hMC3Rs was analyzed by Accuri flow cytometer (Accuri Cytometers, Ann Arbor, MI, USA). The expression levels of the mutant hMC3Rs were calculated as the percentage of WT hMC3R expression using the formula: [mutant - pcDNA3.1] / [WT - pcDNA3.1] ×100%, where the pcDNA3.1 were used as control for background staining ( Wang et al 2008 ; Yang and Tao 2012 ).…”
Section: Methodsmentioning
confidence: 99%
“…The MC4R plays an undisputed role in human obesity pathogenesis since mutations in MC4R have been characterized as the most common monogenic form of obesity in human ( Farooqi et al 2003 ; Hinney et al 2013; Tao 2009 ). However, the role of MC3R in human obesity pathogenesis is more controversial (reviewed in ( Tao 2010b )), although some MC3R mutations (such as I183N and I335S) have been recognized as possible genetic contributors for morbid obesity ( Lee et al 2007 ; Lee et al 2002 ; Mencarelli et al 2008 ; Rached et al 2004 ; Tao 2007 ; Tao and Segaloff 2004 ; Yang et al 2015 ; Yang and Tao 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Decreased total receptor expression has been reported previously for some missense GPCR mutations including the MC4R (Fan & Tao 2009, Wang & Tao 2011, Yang & Tao 2012, Zhang et al 2012, even for some synonymous mutations (Duan et al 2003, Bartoszewski et al 2010. We therefore further studied whether the decreased total receptor expression was due to accelerated protein degradation (Yang et al 2011).…”
Section: Discussionmentioning
confidence: 99%